Constitutional Morality and Military Necessity: The Legitimacy of Sanctions for LGBT Behavior in the Indonesian National Army - Ulum, Bahrul; Juandi, Wawan (LP2M Universitas Ibrahimy, 2026)
This research examines the constitutional legitimacy of imposing sanctions on Indonesian National Armed Forces (TNI) personnel engaging in LGBT conduct within the framework of Indonesia’s Pancasila legal state. While global discourses often advocate for full inclusivity, this study argues that the restriction of such rights in the Indonesian military context is constitutionally valid and strategically justified. Employing a normative legal research method with statutory, conceptual, case, and philosophical approaches, this study analyzes the intersection between human rights, public morality, and defense strategy. The findings reveal three fundamental justifications. First, Pancasila as the Grundnorm and constitutional morality positions religious values and public ethics as legitimate bases for limiting human rights, as explicitly authorized by Article 28J(2) of the 1945 Constitution. Second, under the doctrine of military necessity, the military operates as a lex specialis institution where individual liberties may be curtailed to ensure unit cohesion, command authority, and operational readiness. Third, jurisprudential evidence from military courts demonstrates that sanctions are not directed at sexual orientation as a status, but rather at specific sexual misconduct that disrupts the chain of command and institutional integrity. The study concludes that the dismissal and penalization of LGBT conduct in the TNI are not arbitrary violations of human rights, but proportional measures to uphold the nation's constitutional identity and national defense requirements.